Disease. (16th November 2021) - Baggott, Rob
Abstract: This article examines the significance of the Beveridge report in the light of subsequent developments in health policy and the National Health Service, and considers Beveridge's vision and principles in the context of current and future health challenges. In exploring the post‐war history of health policy and services, it focuses on key themes in the Beveridge report such as prevention, coordination, comprehensive health coverage, funding and the role of the private and voluntary sectors. It argues that in the face of current and future challenges, public health, healthcare and social care should have equal status and an effective system of funding is needed across these three subsystems not only to provide appropriate resources but to ensure that prevention and coordination are prioritised and voluntary action encouraged. In the light of experience, the role of commercial organisations in health and care is more open to challenge. It is also argued that there must also be better coordination of health policy with other spheres of policy making—not just welfare and social policies but economic and environmental policies as well. This agenda requires the kind of joined‐up thinking that Beveridge himself would have applauded.